2010
DOI: 10.1007/s11242-010-9563-2
|View full text |Cite
|
Sign up to set email alerts
|

The Blocking Ability and Flowing Characteristics of Steady Foams in Porous Media

Abstract: Foam flow experiments were carried out to study the influence factors such as surfactant concentration, foam quality, injection rate of liquid and gas, permeability of porous media, temperature, and oil saturation on blocking ability and flowing characteristics of steady foams in porous media. Foam blocking mechanisms and flowing characteristics were summarized according to the experimental results and foam migration behavior. The results showed that the pressure distribution of flowing foams was linearly desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…The foam exhibited shear‐thinning behaviour. Most previous studies of foam flow focused on this range of foam qualities, and concluded that foam presented shear‐thinning in porous media . At higher gas flow rates, the pressure drop nearly remained constant when the foam quality was > 95 %.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The foam exhibited shear‐thinning behaviour. Most previous studies of foam flow focused on this range of foam qualities, and concluded that foam presented shear‐thinning in porous media . At higher gas flow rates, the pressure drop nearly remained constant when the foam quality was > 95 %.…”
Section: Resultsmentioning
confidence: 98%
“…Foam is a complex system in which gas is dispersed in a continuous liquid phase, which is widely used in industrial applications, such as improved oil recovery, matrix acidizing, flotation, and chemical cleaning . Foam can reduce the mobility of the displacing fluid (water or gas) in porous media and block flow paths with higher permeability or fracture .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Foam flooding using foam generated by a mixture of gas (nitrogen, natural gas or other gases) and foaming agents as an oil displacement medium (Pang 2010; Chen et al 2010; Li et al 2010). A lot of works reported that enhanced foam flooding was widely used to further develop this kind of post-polymer flooding reservoirs (Li et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, injection of CO 2 foams was proposed in 1950s to overcome the problems of early gas breakthrough and poor sweep efficiency occurred in the process of pure CO 2 flooding (Bond and Holbrook, 1958). The injection of surfactant solution alternating CO 2 (SAG) and co-injection of surfactant solution and CO 2 has been used to generate foam in the reservoir and thus reduces the mobility of the gas phase and hence increases sweep efficiency (Pang, 2010;Zhang et al, 2013;Chen et al, 2014;Ren et al, 2013). A significant number of researches have been conducted on the application of CO 2 foam as a means of controlling CO 2 mobility and improving sweep efficiency in heterogeneous reservoirs (Khalil and Asghari, 2006;Sohrabi and Farzaneh, 2013;Zhang et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%